Analisis Faktor Risiko Yang Berhubungan dengan Kejadian Diabetes Melitus Tipe 2 di Wilayah Kerja Puskesmas Oesapa Kota Kupang Tahun 2023 - Yuliana Febriani Parera; Indriati A. Tedju Hinga; Yuliana Radja Riwu (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Diabetes Mellitus (DM) is a chronic metabolic disorder, because the pancreas does not produce enough insulin or the body cannot use the insulin produced effectively, resulting in an increase in glucose concentration in the blood. The number of Type 2 DM cases at the Oesapa Health Center in 2023 for the January-May period is 110 cases. The purpose of this study was to analyze the risk factors associated with the incidence of Type 2 Diabetes Mellitus. This study is an analytical observational study using a case control study approach. The research time was carried out for 1 month, namely in June 2023. The samples in this study amounted to 84 samples consisting of two groups, namely case samples of 42 people and control samples of 42 people. The sampling technique uses a simple random sampling technique with a meaning level of α=0.05. The data analysis used in this study was univariate and bivariate analysis using chi square statistical test. Each variable studied was tested using the chi square statistical test to determine the relationship with the variable of Type 2 DM. The results showed a significant relationship between family history (p-value = 0,002; OR=4,462), hypertension (p-value=0,004; OR=4,063) and physical activity (p-value=0,029; OR=2,941) with the incidence of Type 2 DM and there was no significant relationship between smoking (p-value = 0.640) with the incidence of Type 2 DM at the Oesapa Health Center in Kupang City. It is expected that people control blood sugar levels regularly, get used to a healthy lifestyle and increase physical activity through regular exercise such as walking, running, cycling and other physical activities.